Principles of electricity in si units. - MORLEY, Arthur (Logman, 1970)
Units -- Electric current -- Electric circuit -- Electrical resistance -- Electromagnetism -- Electromagnetic induction -- Magnetic circuit -- Inductance in A.D.C circuit -- Electrotastics -- Alternating voltage and current -- Resistance and inductance in A.C. circuits -- Power in an A.C circuits -- Capacitance in an A.C. circuit -- Direct-current machines -- Direct-current generators -- Direct-current motors -- Rectifiers -- Electrical measurements -- Electrolysis: primary and secondary celis